Supramolecular Modulation of Structural Polymorphism in Pathogenic α‐Synuclein Fibrils Using Copper(II) Coordination. Issue 12 (16th February 2018) - Choi, Tae Su; Lee, Jeeyoung; Han, Jong Yoon; Jung, Byung Chul; Wongkongkathep, Piriya; Loo, Joseph A.; Lee, Min Jae; Kim, Hugh I.
Abstract: Structural variation of α‐synuclein (αSyn) fibrils has been linked to the diverse etiologies of synucleinopathies. However, little is known about what specific mechanism provides αSyn fibrils with pathologic features. Herein, we demonstrate Cu(II)‐based supramolecular approach for unraveling the formation process of pathogenic αSyn fibrils and its application in a neurotoxic mechanism study. The conformation of αSyn monomer was strained by macrochelation with Cu(II), thereby disrupting the fibril elongation while promoting its nucleation. This non‐canonical process formed shortened, β‐sheet enriched αSyn fibrils (<0.2 μm) that were rapidly transmitted and accumulated to neuronal cells, causing neuronal cell death, in sharp contrast to typical αSyn fibrils (ca. 1 μm). Our approach provided the supramolecular basis for the formation of pathogenic fibrils through physiological factors, such as brain Cu(II). Abstract : Unlike typical α‐Synuclein (αSyn) fibrillation, copper(II) promotes αSyn nucleation, but retards its elongation. Consequently, highly cell‐transmissible and neurotoxic fibrils are generated through this mechanism. This non‐canonical self‐assembly of αSyn provides the supramolecular basis for generating pathogenic amyloid assemblies.